Analisis Kebutuhan: Perangkat Pembelajaran pada Mata Kuliah Praktik Jurnalistik Media Televisi - Yusandra, Titiek fujita; Rahmi, Afrini; Satini, Ria; Tatalia, Ricci Gemarni (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2022)
Practical activities are carried out to prove a concept being studied. Practical activities following 21st-century learning are a form of learning change, initially centered on educators to become student-centered. Learning tools that are designed and planned according to students' needs certainly create interest so that they can build a productive learning environment. This study aimed to see the student's needs for developing learning tools based on interviews and questionnaires distributed to students who took Praktik Jurnalistik media Televisi course. This type of research was Research and Development (R&D). This research was the initial stage of developing learning tools in Praktik Jurnalistik media Televisi course. The needs analysis results obtained data of 46% stating that learning Praktik Jurnalistik media Televisi can improve speaking skills. 39% of students stated that the journalistic practice module requires development; consequently, the journalistic activities' steps and work processes were structured. 37% of students read and used the module as a guide in journalism practice lectures. Furthermore, 42% of students stated the suitability of the activities of 16 meetings with the learning tools and course syllabus.